Acute cocaine exposure occludes long-term depression in ventral tegmental area GABA neurons. (May 2021) - Friend, Lindsey N.; Wu, Bridget; Edwards, Jeffrey G.
Abstract: The ventral tegmental area (VTA) in the midbrain is essential in incentive salience of reward behavior. Drugs of abuse increase midbrain dopamine cell activity and/or dopamine levels, and can alter endogenous VTA glutamate plasticity, leading to addiction or dependence. VTA dopamine cells are regulated by local inhibitory GABA cells, which exhibit a form of pre-synaptic cannabinoid receptor 1-dependent long-term depression of their glutamatergic inputs. Our current aim was to determine cocaine's influence on VTA GABA cell glutamate plasticity and circuity. Using whole cell voltage-clamp electrophysiology in VTA slices of GAD67-GFP knock-in mice, we recorded excitatory inputs on VTA GABA cells. Acute and chronic injections of cocaine were sufficient to occlude long-term depression. The plasticity could be reversed to the naïve state however, as long-term depression was again observed following a 7-day abstinence from acute cocaine exposure. Furthermore, chronic cocaine decreased AMPA/NMDA ratios at glutamate synapses onto VTA GABA cells, compared to vehicle injection controls, the opposite change noted in dopamine cells. Collectively, our data suggest the cellular mechanism of cocaine-mediated synaptic modification that may result in dependence/withdrawal could involve changes in glutamate input to VTA GABA circuitry in addition to VTA dopamine cells. Therefore VTA GABA cells may also play a role, possibly in a synergistic manner with the dopamine circuit, in cocaine-induced changes to the VTA reward pathway than previously known.